A structural investigation of the sulphated polysaccharide from Aeodes ulvoidea Schmitz - Allsobrook, Anthony John Robert (Rhodes University, Faculty of Science, Department of Chemistry, 1973)
Aeodes ulvoidea, a red seaweed of the Grateloupiaceae, yielded a highly sulphated polysaccharide which was shown to contain D- and L-galactose, 4-0-methy-L-galactose, 2-0-methyl - D- and L-galactose and 6-0-methyl-D-galactose, together with chromatographic traces of xylose and mannose. The sulphate was not labile to alkali, but it was largely removed with methanolic hydrogen chloride. Periodate oxidation of the polysaccharide, methylation of the de sulphated polysaccharide, and investigation of fifteen oligosaccharides from partial hydrolysis and acetolysis studies of the polysaccharide, indicate that (a) the polysaccharide is composed of a backbone of D-galactose residues which are 1,3- and 1,4-linked (b) at least some regions of alternating structure do occur (c) the 2-0-methylgalactose is linked through the 4-position (d) the 4-0-methyl-L-galactose is present as single unit side chains glycosidically linked to the galactose backbone at position 6, and (e) most of the 6-0-methyl-D-galactose is linked to the 4-position of 2-0-methyl-D-galactose.
Keywords: Red algae -- Composition; Polysaccharides